The genus Alcyonium (Octocorallia: Alcyonacea: Alcyoniidae) in Chile - van Ofwegen, L. P.; Häussermann, V.; Försterra, G. (Zootaxa, 2007)
Four new species of Alcyonium (Octocorallia: Alcyoniidae) are described from Chile. They occur in the shallow waters of the southern fjord region. One of them is an encrusting species, the other three form digitate colonies. Encrusting forms of A. grandis Casas et al., 1997, and A. haddoni Wright & Studer, 1889 were also found in the fjord region, bringing the number of Alcyonium species recorded for Chile to eight. For all six recently collected species SEM images of sclerites are presented, and a key to the Chilean Alcyonium species is included.